Expert information-analytical system as a method of strategic management of the process of psychological preparation in sports - Banayan, A. A.; Malinin, A. V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop the structure of an expert information-analytical system for the psychological support of athletes.